1989
DOI: 10.1042/bj2570399
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin as a potent effector of adipose-cell differentiation

Abstract: The terminal differentiation of Ob1771 pre-adipose cells induced by arachidonic acid in serum-free hormone-supplemented medium containing insulin, transferrin, growth hormone, tri-iodothyronine and fetuin (5F medium) was strongly diminished in the presence of inhibitors of prostaglandin synthesis, namely aspirin or indomethacin. Carbaprostacyclin, a stable analogue of prostacyclin (prostaglandin I2) known to be synthesized by pre-adipocytes and adipocytes, behaved as an efficient activator of cyclic AMP produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(68 citation statements)
references
References 33 publications
3
65
0
Order By: Relevance
“…The metabolites of PGJ2, AI~-PGJ2 and 15-deoxy-Aa2,14-pGJ2, were also found to be inactive (not shown). It is striking that PGE1 and 6-keto-PGE1 were inactive despite their binding to the same cell surface receptor as PGI2 [34,35], and their ability to alter intracellular cAMP and free calcium levels [10] and to induce the terminal differentiation of Ob 1771 preadipose cells, although to a lower extent than cPGI2 [2]. Moreover, simultaneous exposure to an adenylate cyclase agonist (forskolin) and a calcium ionophore (ionomycin), which are able to mira- of cPGIz with the glucocorticoid nuclear receptor, if any, had to be excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolites of PGJ2, AI~-PGJ2 and 15-deoxy-Aa2,14-pGJ2, were also found to be inactive (not shown). It is striking that PGE1 and 6-keto-PGE1 were inactive despite their binding to the same cell surface receptor as PGI2 [34,35], and their ability to alter intracellular cAMP and free calcium levels [10] and to induce the terminal differentiation of Ob 1771 preadipose cells, although to a lower extent than cPGI2 [2]. Moreover, simultaneous exposure to an adenylate cyclase agonist (forskolin) and a calcium ionophore (ionomycin), which are able to mira- of cPGIz with the glucocorticoid nuclear receptor, if any, had to be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Among prostanoids, a potent and specific adipogenic role has been delineated for carbaprostacyclin (cPGI2) and other stable analogues of prostacyclin (PGI2) [2][3][4], which is one of the major metabolites of arachidonic acid in both preadipose and adipose cells [5][6][7][8]. On a short-term basis both PGI2 and its stable analogue cPGI2 play a similar dual role in eliciting elevation of intracellular cAMP and free Ca 2÷ [9,10] and, in addition, are equally active on a long-term basis in triggering terminal differentiation of preadipose to adipose cells ( [2] and J. Aubert et al, unpublished results), cPGI2 has indeed been shown to specifically promote terminal differentiation not only of preadipocytes from clonal lines but also that of adipose precursor cells isolated from murine or human adipose tissue and maintained in primary culture under chemically defined, serum-free conditions [4,11]. Moreover, PGI~ behaves as an autocrine/paracrine effector of adipose cell differentiation in vitro by means of binding to its cell surface receptor [3,4,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Because this PG can stimulate the synthesis of TGFα in rat preadipocytes, the existence of an amplification mechanism between these two differentiation inhibitors has been postulated [199]. By contrast, carbaprostacyclin (cPGI 2 ), a stable analogue of PGI 2 , is recognized as a strong auto-/paracrine adipogenic agent for Ob1771 cells as well as for primary rodent and human preadipocytes [40,170,245,247]. In addition to PGI 2 , PGD 2 and its derivative PG 15-deoxy-J 2 may be endogenous ligands for PPARγ [117,142].…”
Section: The Prostaglandinsmentioning
confidence: 99%
“…13 Among fatty acids, arachidonic acid was characterized as a major adipogenic factor puri®ed from serum 14 and further studies showed that this essential fatty acid is mainly active as a precursor of prostacyclin. 15 Prostacyclin or its stable analog carbacyclin trigger the terminal differentiation of mouse preadipose cells from Ob17 clonal line, whereas carbacyclin increases the differentiation of rat and human preadipocytes in primary culture. 16 We assume that prostacyclin plays a key and speci®c role locally in the differentiation of adipose precursor cells as: (i) preadipose cells synthetize prostacyclin 17 and express simultaneously the cell surface prostacyclin receptor (IP-R); 16 adipose cells become unresponsive to prostacyclin 16 but remain able to synthesize this eicosanoid only after stimulation by angiotensin II; 18 (ii) compared to prostacyclin, other prostaglandins (PGE 1 and 6-keto-PGE 1 ), are also able to both bind to the IP-R and alter intracellular cAMP and Ca 2 levels, exhibit weak adipogenic properties; 19 and (iii) prostacyclin has been identi®ed as the chemical relay allowing a`cross-talk' between adipose and preadipose cells both in vitro 18 and in vivo (R Ne Âgrel et al, unpublished results).…”
Section: Secreted Factors and Endocrine Functionsmentioning
confidence: 99%